Department of Foreign Affairs history - Foreign Service Institute ([Manila The Institute], 1995)
A documentary on the history of the Department of Foreign Affairs set within the larger context of the history of Philippine foreign relations.
VHS.
A project of the Foreign Service Institute.
Keywords: Political science